READING COMPREHENSION DIFFICULTIES AMONG TENTH GRADE STUDENTS OF VOCATIONAL HIGH SCHOOL - ESTER RENTA JELITA BUTARBUTAR; Fahri Haswani (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2021)
In regard to the need for reading comprehension ability in the school, the objective of this research is to identify: (1) the difficulties faced by tenth grade students of Vocational High School in reading comprehension and (2) the factors influencing students’ reading comprehension difficulties. This research used both questionnaire and interview as the instruments of data collection. The data was analyzed based on the theory of Nuttal (1982) which reducing it by categorizing the relevant data. The participants of this study were tenth grade students of a Vocational High School in Medan. In doing this research, the procedures were gathering the data and information, reducing data, and drawing conclusion. The result of the research showed that: (1) most of the students have difficulties in determining main idea, locating reference, understanding vocabulary, and making inference and (2) the factors influencing their difficulties were limited vocabulary knowledge, lack of fluency, lack of familiarity of the subject matter, and the problems in recalling after reading. The result of this research is expected to be beneficial for English teachers to identify their students’ difficulties in reading comprehension in order to have innovation or appropriate strategies in teaching reading and this research also can be useful for the students to be able to know their difficulties in reading skill.